Pore pressure/stress coupling in Brunei Darussalam - implications for shale injection - Tingay, Mark; Swarbrick, R.; Okpere, E. (Geological Society of London, 2003)
Shale dykes, diapirs and mud volcanoes are common in the onshore and offshore regions of Brunei Darussalam. Outcrop examples show that shale has intruded along both faults and tensile fractures. Conventional models of over pressure-induced brittle failure assume that pore pressure and total stresses are independent of one another. However, data worldwide and from Brunei show that changes in pore pressure are coupled with changes in total minimum horizontal stress. The pore pressure/stress-coupling ratio describes the rate of change of minimum horizontal stress magnitude with changing pore pressure. Minimum horizontal stress measurements for a major offshore field where undepleted pore pressures range from normal to highly overpressured show a pore pressure/stress-coupling ratio of 0.59. As a consequence of pore pressure/stress coupling, rocks can sustain a greater increase in pore pressure prior to failure than predicted by the prevailing values of pore pressure and stress. Pore pressure/stress-coupling may favour the formation of tensile fractures with increasing pore pressure rather than reactivation of pre-existing faults. Anthropogenically-induced tensile fracturing in offshore Brunei supports this hypothesis.